2016
DOI: 10.1098/rspb.2016.1136
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of transgenerational immunity in invertebrates

Abstract: Over a decade ago, the discovery of transgenerational immunity in invertebrates shifted existing paradigms on the lack of sophistication of their immune system. Nonetheless, the prevalence of this trait and the ecological factors driving its evolution in invertebrates remain poorly understood. Here, we develop a theoretical host -parasite model and predict that long lifespan and low dispersal should promote the evolution of transgenerational immunity. We also predict that in species that produce both philopatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 67 publications
1
65
2
Order By: Relevance
“…It was noticed over a decade ago that infection of a mother increases resistance in her offspring in insects [54,55] . Such transgenerational immune priming is particularly important in social insects that typically live in dense colonies and have low dispersal [56] . Trans-generational immune priming is familiar in vertebrates, where antibodies are the carriers of immunological memory from mother to offspring.…”
Section: Vitellogenin In Transgenerational Immune Primingmentioning
confidence: 99%
“…It was noticed over a decade ago that infection of a mother increases resistance in her offspring in insects [54,55] . Such transgenerational immune priming is particularly important in social insects that typically live in dense colonies and have low dispersal [56] . Trans-generational immune priming is familiar in vertebrates, where antibodies are the carriers of immunological memory from mother to offspring.…”
Section: Vitellogenin In Transgenerational Immune Primingmentioning
confidence: 99%
“…; Rechavi ; Pigeault et al. ). Our model predicts that parents would be selectively favored to produce more even mixtures of offspring resistant to one parasite strain versus another, while offspring themselves favor resistance against the parasite that is commonest in current local environment.…”
Section: Discussionmentioning
confidence: 99%
“…One possible example is when individuals bet-hedge defenses against multiple stressors, as they do when resistance to one strain of parasite trades off against resistance to another strain (strain-specific immunity: Little et al 2003;Schmid-Hempel 2005). While resistance in such contexts is often studied in the context of heterozygosity (e.g., Penn et al 2002), an accumulating number of studies have shown that parasite resistance is, in part, influenced by transgenerational effects (Little et al 2003;Boulinier and Staszewski 2008;Roth et al 2009;Rechavi 2014;Pigeault et al 2016). Our model predicts that parents would be selectively favored to produce more even mixtures of offspring resistant to one parasite strain versus another, while offspring them-selves favor resistance against the parasite that is commonest in current local environment.…”
Section: Discussionmentioning
confidence: 99%
“…Parental investment, resource allocation, and life‐history theories postulate that adults who can accurately perceive their surroundings and anticipate the needs of future offspring based on their own experiences, will be selected to transfer information to their progeny in a context‐dependent fashion (Badyaev, ; Mousseau, ; Mousseau & Fox, ; Sorci & Clobert, ; Uller, ). Through such tailored contributions, parents can help match the needs of future offspring to the environmental pressures they are likely to encounter (Houri‐Ze'evi et al., ; Pigeault, Garnier, Rivero, & Gandon, ; Poulin & Thomas, ; Sorci & Clobert, ; Storm & Lima, ). Infectious agents are among the most prevalent environmental cues known to trigger nongenetic maternal and paternal effects (Freitak et al., ; Poulin & Thomas, ; Sadd, Kleinlogel, Schmid‐Hempel, & Schmid‐Hempel, ; Salmela, Amdam, & Freitak, ; Trauer‐Kizilelma & Hilker, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Infectious agents are among the most prevalent environmental cues known to trigger nongenetic maternal and paternal effects (Freitak et al., ; Poulin & Thomas, ; Sadd, Kleinlogel, Schmid‐Hempel, & Schmid‐Hempel, ; Salmela, Amdam, & Freitak, ; Trauer‐Kizilelma & Hilker, , ). Based on their pathogenic history and/or immunological state, parents may protect the next generation by either direct passive transfer of immune function (transgenerational immunity [TGI]) or indirectly through the transfer of molecules that trigger the progeny's own immune system (transgenerational immune priming [TGIP]), rendering offspring less susceptible to the same pathogens experienced by their parents (Freitak et al., ; Marshall & Uller, ; Pigeault et al., ; Roth et al., ; Sadd et al., ; Sorci & Clobert, ). Both TGI and TGIP have been mostly studied at the phenomenological level in a variety of taxonomic groups and appear to be triggered by diverse pathogenic microbes and immune elicitors (Freitak, Heckel, & Vogel, ; Grindstaff et al., ; Hernández López, Schuehly, Crailsheim, & Riessberger‐Gallé, ; Little, O'Connor, Colegrave, Watt, & Read, ; Lozano & Ydenberg, ; Moret, ; Roth et al., ; Sadd & Schmid‐Hempel, ; Sadd et al., ; Tidbury, Pedersen, & Boots, ; Trauer‐Kizilelma & Hilker, , ; Zanchi, Troussard, Martinaud, Moreau, & Moret, ; Zanchi, Troussard, Moreau, & Moret, ).…”
Section: Introductionmentioning
confidence: 99%